Pericytes in Cerebrovascular Diseases: An Emerging Therapeutic Target - Su, Xiaojuan; Huang, Lingyi; Qu, Yi; Xiao, Dongqiong; Mu, Dezhi (Frontiers in Cellular Neuroscience, 2019)
Pericytes are functional components of the neurovascular unit that are located around the blood vessels, and their roles in the regulation of cerebral health and diseases has been reported. Currently, the potential properties of pericytes as emerging therapeutic targets for cerebrovascular diseases have attracted considerable attention. Nonetheless, few reviews have comprehensively discussed pericytes and their roles in cerebrovascular diseases. Therefore, in this review, we not only summarized and described the basic characteristics of pericytes but also focused on clarifying the new understanding about the roles of pericytes in the pathogenesis of cerebrovascular diseases, including white matter injury, hypoxic–ischemic brain damage, depression, neovascular insufficiency disease, and Alzheimer’s disease. Furthermore, we summarized the current therapeutic strategies targeting pericytes for cerebrovascular diseases. Collectively, this review is aimed at providing a comprehensive understanding of pericytes and new insights about the use of pericytes as novel therapeutic targets for cerebrovascular diseases.